Droplet Ejection and Liquid Jetting by Visible Laser Irradiation in Pyro‐Photovoltaic Fe‐Doped LiNbO3 Platforms. Issue 22 (25th October 2021) - Puerto, Andrés; Coppola, Sara; Miccio, Lisa; Vespini, Veronica; García‐Cabañes, Ángel; Carrascosa, Mercedes; Ferraro, Pietro
Abstract: Controlling liquid dispensing and jetting from a reservoir drop or a liquid film require strong electric fields. One efficient method proposed some years ago is based on the high pyroelectric‐electrohydrodynamic (EHD) effect presented by lithium niobate when it undergoes a high temperature change. Additionally, first experiments generating droplets using the photovoltaic effect of Fe‐doped lithium niobate crystal (LiNbO3 :Fe) have been recently reported. Here, it is shown how the excitation of the photovoltaic and pyroelectric effects of LiNbO3 :Fe by visible light irradiation allows droplet dispensing and jetting. A basic characterization of the process, including the important role of the excitation light intensity, is reported. The experimental investigation demonstrates that efficient droplet ejection and liquid jetting can be easily achieved in different optical configurations and with various liquid solutions (water, alcohol, aqueous suspension of particles or polymers). This new explored method is analyzed by discussing some of its intrinsic and attractive advantages, namely the flexible and versatile control offered by light excitation and the activation of the photovoltaic and pyroelectric effects. The results let us to foresee that this strategy will have very good chances to become a viable inkjet printing method for addressing new challenges in directed liquid dispensing and patterning. Abstract : The visible laser irradiation in pyro‐photovoltaic Fe‐doped LiNbO3 platforms addresses efficient droplet ejection and liquid jetting in different optical configurations and with various liquid solutions (water, alcohol, and aqueous suspension of particles or polymers). The multiplexing properties simplify the jetting activation in case of a matrix of droplets of different materials in a completely contact‐free mode.